(untitled) (Medico Legal Update, 2020)
Rape is a serious offence and understanding the offender may help us to understand the antecedents leading (directly or indirectly) to the act. The examination of the survivors of alleged sexual offences is one of the most difficult tasks in Medical practice. Methodology: This study was carried out between January 2012 to June 2013 in the Department of Forensic Medicine at Tertiary care centre, South Bangalore, Karnataka. The cases registered under sections 375, 376 IPC and Protection of Children from Sexual Offences Act were included in the study. Results: Total 38 accused were examined during study period. 55.3% of cases were in the age group of 21 years to 30 years. 57.9% of cases were graduated, and 34.2% were employed. 44.7% cases belong to lower middle class (III). In 47.5 % of cases the incident occurred between evening & mid night time. Offender was close friends of the victim in 47.5% cases. Non genital external injuries were present in 5.3% of cases. Discussion: Young adult males were involved in majority of cases due to their immature mind set. Majority of the offenders were close friends of the victim, and were booked due to stringent provisions of POCSO Act. Consensual sexual activity between teenagers can be decriminalized.